The Application of Finger Painting Games to Children's Fine Motor Development in Kb Nurul Barokah, Wangkal Village, Gading District, Probolinggo District - Zahro, Fatimatus; Wisudaningsih, Endah Tri; Purnamasari, Debby Adelita Febrianti (Jurnal Indonesia Sosial Sains, 2024)
One of the basic skills that children need to develop is motor skills, which consist of two parts: gross motor skills and fine motor skills. The problem raised in this research is how to apply the fingerpainting game to develop fine motor skills in children, and the research aims to find out whether the fingerpainting game can develop children's fine motor skills at KB Nurul Barokah, Wangkal Village. The analytical method used in this work is a qualitative descriptive research approach, with data collection techniques through observation, interviews and documentation. The data analysis techniques used are data collection, data condensation, data presentation and conclusions. They are checking the validity of the data through data credibility tests, transferability tests, dependability tests, and confirmability tests. The results of this research show the development of all aspects of children, excellent physical aspects of fine motor skills through finger painting activities; children can also carry out other tasks such as buttoning their clothes, wearing their shoelaces, peeling their peanut shells and being able to hold a pencil correctly. Correct. This article proves that the fingerpainting game method can improve children's fine motor skills at KB Nurul Barokah Wangkal Gading.